Vitamin D receptor, vitamin D binding protein and CYP27B1 single nucleotide polymorphisms and susceptibility to viral infections in infants - Maria Zacharioudaki (Nature Portfolio, 2021)
Abstract The role of vitamin D in innate and adaptive immunity is recently under investigation. In this study we explored the potential association of genetic variances in vitamin D pathway and infections in infancy. Τhis prospective case–control study included infants 0–24 months with infection and age-matched controls. The single nucleotide polymorphisms of vitamin D receptor (VDR) gene (BsmI, FokI, ApaI, TaqI), vitamin D binding protein (VDBP) (Gc gene, rs7041, rs4588) and CYP27B1 (rs10877012) were genotyped by polymerase chain reaction-restriction fragment length polymorphism. In total 132 infants were enrolled, of whom 40 with bacterial and 52 with viral infection, and 40 healthy controls. As compared to controls, ΤaqI was more frequent in infants with viral infection compared to controls (p = 0.03, OR 1.96, 95% CI 1.1–3.58). Moreover, Gc1F was more frequent in the control group compared to infants with viral infection (p = 0.007, OR 2.7, 95% CI 1.3–5.6). No significant differences were found regarding the genetic profile for VDR and VDBP in infants with bacterial infection compared to the controls and also regarding CYP27B1 (rs10877012) between the studied groups. Genotypic differences suggest that vitamin D pathway might be associated with the host immune response against viral infections in infancy.